PENGARUH IMPULS ARUS TERHADAP GELOMBANG ELEKTROMAGNETIK RADIO FM - , BONDAN RESPATI, Dr. Ir. T. Haryono, M.Sc., C.Eng., MIET ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lightning is a natural phenomenon that vomits electric charge current and voltage with a very large value in a very short time. High voltage transmission line is rarely impaired due to lightning strikes whichâs voltage level is almost equal to the transmission voltage level. However, when lightning strikes lowvoltage lines close to distribution line customers (home), the voltage and current transients caused by lightning will have an impact on the electrical system at the customer (home) and can make a damage for low voltage equipment and electronics. There are two kinds of lightning strikes, which are the direct and indirect lightning strike. The metode that used in this research is the indirect lightning strikes, which is concentrate on the effect of electromagnetic field by current impulse that simulated by the impulse generator and then the transient voltage will be inducted the low voltage utilities nearby. With aseries of studies that have done, thenthe data will transformintothe parametersandvariablesthat directsresearchon the purposeof thisstudy, thedata processingwill be knownthe phenomenon ofwhat isgoing on inthe radioas the objectused. The resultsofthis studywillbe proventhat theeffectsofindirect lightningimpulsecurrentsat a voltage leveldonotharmthe radio.